ANALISIS TERHADAP HADIS KISAH ORANG YANG BERPENYAKIT LEPRA, BERKEPALA BOTAK DAN ORANG BUTA YANG DIUJI OLEH ALLAH SEBAGAI BENTUK EVALUASI AFEKTIF DALAM PENDIDIKAN ISLAM - Salmah, Salmah (State Institute for Islamic Studies Batusangkar, 2017)
In Islamic education, evaluation is one component of the Islamic education system that must be done systematically and planned as a tool to measure success or targets to be achieved in the process of Islamic education and learning process that is expected to be achieved by learners. Evaluation in Islamic education certainly refers to the source of Islamic teachings themselves, namely Qur'an and Hadith. Related to the source of Islamic teachings both forms of evaluation are contained in many hadiths conveyed by the Prophet, whether in the form of stories or stories or in the form of the words of the Prophet when evaluating the Companions to the tasks that have been mandated to them or evaluating the memorization or knowledge of friends who have taught the Prophet, and various other forms of evaluation contained in the hadiths of the Prophet contained in various books of hadith. To obtain information on this tradition is done tracking by using takhrîj method of hadith, so will be met the hadiths of the Prophet who contains stories that contain elements of evaluation in various books of Hadith. These hadiths analyzed the quality of their history and linked it with evaluation in Islamic education.